Reciprocal Responses in the Interaction between Arabidopsis and the Cell-Content-Feeding Chelicerate Herbivore Spider Mite. Issue 1 (27th November 2013) - Zhurov, Vladimir; Navarro, Marie; Bruinsma, Kristie A.; Arbona, Vicent; Santamaria, M. Estrella; Cazaux, Marc; Wybouw, Nicky; Osborne, Edward J.; Ens, Cherise; Rioja, Cristina; Vermeirssen, Vanessa; Rubio-Somoza, Ignacio; et al.
Abstract : Analysis of genome-wide Arabidopsis responses to spider mite identifies the secondary metabolites that limit the mite's ability to use Arabidopsis as a host . Abstract: Most molecular-genetic studies of plant defense responses to arthropod herbivores have focused on insects. However, plant-feeding mites are also pests of diverse plants, and mites induce different patterns of damage to plant tissues than do well-studied insects (e.g. lepidopteran larvae or aphids). The two-spotted spider mite ( Tetranychus urticae ) is among the most significant mite pests in agriculture, feeding on a staggering number of plant hosts. To understand the interactions between spider mite and a plant at the molecular level, we examined reciprocal genome-wide responses of mites and its host Arabidopsis ( Arabidopsis thaliana ). Despite differences in feeding guilds, we found that transcriptional responses of Arabidopsis to mite herbivory resembled those observed for lepidopteran herbivores. Mutant analysis of induced plant defense pathways showed functionally that only a subset of induced programs, including jasmonic acid signaling and biosynthesis of indole glucosinolates, are central to Arabidopsis's defense to mite herbivory. On the herbivore side, indole glucosinolates dramatically increased mite mortality and development times. We identified an indole glucosinolate dose-dependent increase in the number of differentially expressed mite genes belonging to pathways associated with detoxification of xenobiotics. This demonstrates that spider mite is sensitive to Arabidopsis defenses that have also been associated with the deterrence of insect herbivores that are very distantly related to chelicerates. Our findings provide molecular insights into the nature of, and response to, herbivory for a representative of a major class of arthropod herbivores.